Manajemen Implementasi Standar Isi untuk Peningkatan Mutu Pembelajaran pada MTsN 4 Tabalong Provinsi Kalimantan Selatan - Rasma Afifah; Siti Mas'amah; Nahdiyatul Husna; Teddy Suryana,; Hanafiah Hanafiah; Sri Handayani (LPPM Institut Nasional Laa Roiba Bogor, 2023)
Basically all madrasas are obliged to make quality assurance efforts to meet and even exceed national education standards. To guarantee and control the quality of education, evaluation, accreditation, and certification are carried out. However, in reality there are still many madrasas that have not made serious efforts to carry out these obligations. Efforts that need to be made by madrasas to meet national education standards which include content standards, process standards, graduate competency standards, facilities and infrastructure standards, management standards, financing standards, educators and education personnel standards, and assessment standards. Strategies that need to be implemented by madrasas to meet national education standards, especially by utilizing all potential, compiling work plans and programs as needed, encouraging all components of madrasas to improve their performance, forming a quality assurance team, fixing learning tools, enforcing madrasa rules, expanding cooperation with the business world and industry, madrasa committees, supervisors, and the government, facilitate teachers and education personnel to improve competence, evaluate every activity that has been carried out, and document all evidence of madrasa activities. Keywords: Content Standards, Education Quality Assurance